2021
DOI: 10.1159/000520734
|View full text |Cite
|
Sign up to set email alerts
|

Association of <b><i>PNPLA3</i></b> I148M with Liver Disease Biomarkers in Latinos

Abstract: Introduction. Liver disease accounts for approximately 2 million deaths per year worldwide. The majority of liver diseases are due to complications of cirrhosis, viral hepatitis, and hepatocellular carcinoma. Increased levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) may indicate liver disease. Moreover, there are additional noninvasive liver fibrosis indices that help to estimate liver damage, including AST to ALT ratio, AST to platelet ratio index (APRI), fibrosis-4 (FIB-4) score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(48 reference statements)
0
5
0
1
Order By: Relevance
“…Our Kaplan‐Meier curves show that the PNPLA3 GG genotype increased de novo HCC in our female patients. Recent studies including Caucasian, African, and Latino patients have shown similar results: women with the PNPLA3 G‐allele had a significantly higher probability of steatosis or fibrosis than did men 26–28 . Although the mechanism remains unclear, the main hypothesis for this finding is that the effect of PNPLA3 may be amplified by an interaction with female sex hormones 29 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our Kaplan‐Meier curves show that the PNPLA3 GG genotype increased de novo HCC in our female patients. Recent studies including Caucasian, African, and Latino patients have shown similar results: women with the PNPLA3 G‐allele had a significantly higher probability of steatosis or fibrosis than did men 26–28 . Although the mechanism remains unclear, the main hypothesis for this finding is that the effect of PNPLA3 may be amplified by an interaction with female sex hormones 29 .…”
Section: Discussionmentioning
confidence: 66%
“…In fact, despite steatosis having been proven to be a risk factor for HCC G-allele had a significantly higher probability of steatosis or fibrosis than did men. [26][27][28] Although the mechanism remains unclear, the main hypothesis for this finding is that the effect of PNPLA3 may be amplified by an interaction with female sex hormones. 29 In a study of CHC patients who achieved SVR before or after the application of a DAA, Miki et al reported that the PNPLA3 CG/GG genotype increased de novo HCC in the absence of metabolic disorders associated with HCC, such as obesity and diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…The PNPLA3 I148M allele is found most commonly in Hispaniic individuals, then European individuals, and then non-Hispanic Black individuals [42,43] Within Hispanic populations, the PNPLA3 I148M allele is associiated with elevated levels of AST, ALT, FIB-4 score, and increased risk of MASLD [44][45][46][47][48] The frequency of the PNPLA3 I148M allele varies among Hispanicc groups, with Mexican individuals having the highest frequency, followed by South Americans, Central Americans, Puerto Ricans, Cubans, and lastly Dominicans [48] Within Hispanic populations, low plasma concentrations of very long chain n-3 polyunsaturated fatty acids and very long chain saturated fatty acids are rongly associated with advanced liver fibrosis [51,52] There is a positive association between exposures including arsenic and mercury and risk of MASLD, with the highest exposure seen among Mexican Americans and those of Hispanic ethnicity [58,59] Behavioral risk factors, including high-fat, high-carbohydrate diet and sedentary behavior, are risk factors for all populations to develop MASLD,regardless of race and ethnicity polymorphisms associated with MASLD risk and progression. The most notable single nucleotide polymorphism (SNP) associated with MASLD is the gene that codes for PNPLA3.…”
Section: Key Finding Sourcesmentioning
confidence: 99%
“…The 1,000 Genomes Project Study, published in 2015, utilized whole-genome sequencing in 2,504 individuals from 26 populations and found that the distribution of the PNPLA3 I148M allele varies globally, with the M variant being most common in populations of Hispanic and East Asian ancestry [43] . Multiple studies support that the PNPLA3 I148M allele (rs738409) variant is associated with increased levels of ALT, AST, and FIB-4 score in Hispanic individuals, including a study of 503 Hispanic adult participants from the Arizona Insulin Resistance (AIR) registry and a study published in 2023 of 8,739 adult Hispanic participants from the BioMe biobank [44,45] .…”
Section: Key Finding Sourcesmentioning
confidence: 99%
“…Развитие НАЖБП исследователи связывают с рядом однонуклеотидных полиморфизмов, в частности выявлена связь полиморфизма гена PNPLA3 (patatin like phospholipase domain containing 3) p.I148M (rs738409 C>G) с развитием стеатоза [4]. Более частое развитие ГЦР также может указывать на вероятную связь полиморфизма гена PNPLA3 и ГЦР на фоне НАЖБП [5]. Особое внимание обращается на носительство минорного аллеля G как на фактор риска развития агрессивных форм течения НАЖБП [6].…”
Section: Introductionunclassified